Transformational Leadership in Muhammadiyah Association for Community Growth - Romadhona, Ferina; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
Background: Transformational leadership is vital in educational settings, focusing on inspiring members to enhance performance. Specific Background: At Universitas Muhammadiyah Sidoarjo, key leaders, including the Rector, play a crucial role in creating an effective academic environment. Knowledge Gap: There is limited empirical evidence on the impact of transformational leadership on organizational performance and faculty motivation in this context. Aims: This study investigates the characteristics and effects of transformational leadership, emphasizing individualized consideration and motivational strategies. Results: The findings reveal that the Rector's leadership positively influences faculty motivation and recognition, illustrated by rewards like Umrah allowances. Novelty: This research enriches existing literature by analyzing transformational leadership within a specific educational framework. Implications: The study highlights the significance of leader recognition in higher education, suggesting that transformational practices can enhance faculty performance and promote a culture of excellence. Highlights : Impact on Motivation: Transformational leadership enhances faculty motivation through recognition and rewards. Leadership Characteristics: The Rector exemplifies individualized consideration, actively supporting faculty development. Cultural Improvement: Effective leadership fosters a culture of excellence and innovation within the institution. Keywords: transformational leadership, Muhammadiyah, faculty motivation, individualized consideration, higher education